06.07 Disease-inducible interleukin-10 gene therapy suppresses innate cytokine response in the 3d micromass model of the synovial membrane. (1st March 2017) - Broeren, Mathijs GA; Bennink, Miranda B; Arntz, Onno J; van den Berg, Wim B; van de Loo, Fons AJ
Abstract : Background: No disease-modifying drugs are available for osteoarthritis (OA). Although the aetiology is still unknown, inflammation is indicated to be involved in the disease pathogenesis in many patients. Gene therapy can enable transduced joint cells to express an anti-inflammatory biological drug with long-lasting bioavailability. In addition, off-target effects can be further reduced by regulating the expression using a disease-responsive promoter that is only active during disease flares. Clinical studies in chronic diseases with anti-inflammatory recombinant Interleukin-10 (IL-10) are impeded by its short half-life. Disease-inducible gene therapy might therefore be the ideal system to provide IL-10 in an OA joint in a regulated fashion. The objective of this study was to test the feasibility of this approach in a human in-vitro model of the synovial membrane. Methods: Cell suspensions of digested joint biopsies were mixed with Matrigel to form micromasses, in which the cells migrate to the surface. The micromasses were transduced with a lentiviral vector containing the IL-10 gene under control of the inflammation-sensitive CXCL10 promoter (CXCL10p-IL10) or the constitutive active PGK promoter (PGK-IL10). Subsequently, micromasses were stimulated with inflammatory triggers Tumour Necrosis Factor-alpha (TNFα) and lipopolysaccharide (LPS). Gene expression effects were determined by qPCR and the production of cytokines by the synovial micromasses was measured by multiplex ELISA. Results: In 1 week cultured micromasses, migrated cells formed a lining containing both synovial fibroblasts and macrophages similar to that seen in the synovium. This lining could be efficiently targeted by lentiviruses. After stimulation with LPS and TNFα, the production of CXCL10-controlled IL-10 expression increased by 9.7-fold and 7.2-fold respectively. The IL-10 production after transduction with PGK-IL10 was not influenced by proinflammatory stimulation. The induced levels of IL-10 were high enough to significantly reduce the production of IL-1β and IL-6 by the micromasses. The anti-inflammatory effect of CXCL10-controlled IL-10 might be mediated by SOCS3. Recombinant IL-10 increased SOCS3 expression by 3.0-fold 2 hour after stimulation. Conclusions: This study on primary human synovial micromasses suggest that the CXCL10p-IL-10 gene therapeutic approach to suppress the innate cytokine response in the osteoarthritic joint might be a feasible approach for local treatment of OA.